Robotic kidney transplantation in the obese patient: 10‐year experience from a single center. Issue 2 (24th December 2019) - Tzvetanov, Ivo G.; Spaggiari, Mario; Tulla, Kiara A.; Di Bella, Caterina; Okoye, Obi; Di Cocco, Pierpaolo; Jeon, Hoonbae; Oberholzer, Jose; Cristoforo Giulianotti, Pier; Benedetti, Enrico
Abstract : Despite increasing obesity rates in the dialysis population, obese kidney transplant candidates are still denied transplantation by many centers. We performed a single‐center retrospective analysis of a robotic‐assisted kidney transplant (RAKT) cohort from January 2009 to December 2018. A total of 239 patients were included in this analysis. The median BMI was 41.4 kg/m 2, with the majority (53.1%) of patients being African American and 69.4% of organs sourced from living donors. The median surgery duration and warm ischemia times were 4.8 hours and 45 minutes respectively. Wound complications (mostly seromas and hematomas) occurred in 3.8% of patients, with 1 patient developing a surgical site infection (SSI). Seventeen (7.1%) graft failures, mostly due to acute rejection, were reported during follow‐up. Patient survival was 98% and 95%, whereas graft survival was 98% and 93%, at 1 and 3 years respectively. Similar survival statistics were obtained from patients undergoing open transplant over the same time period from the UNOS database. In conclusion, RAKT can be safely performed in obese patients with minimal SSI risk, excellent graft function, and patient outcomes comparable to national data. RAKT could improve access to kidney transplantation in obese patients due to the low surgical complication rate. Abstract : The authors report minimal surgical site infections and wound complications, with graft and patient survival comparable to national databases, in an analysis of robotic kidney transplant in obese patients from a single institution.